The shadow returns - Charman, Katrina; Tondora, Judit (New York : Branches/Scholastic Inc., 2023)
Skull, the Shadow, and a few of the rat army escaped into Perodia, and now Tag and the other defenders must locate them, and also find their friend, Bod, who is still trapped in the Underland with the rest of the rat army.
Grades 2-3.
650L
Keywords: Owls -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Magic -- Juvenile fiction; Labyrinths -- Juvenile fiction; Owls -- Fiction; Squirrels -- Fiction; Mythical animals -- Fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Animal fiction; Action and adventure fiction; Fantasy fiction